Elevated Abundance, Size, and MicroRNA Content of Plasma Extracellular Vesicles in Viremic HIV-1+ Patients: Correlations With Known Markers of Disease Progression. (1st November 2015) - Hubert, Audrey; Subra, Caroline; Jenabian, Mohammad-Ali; Tremblay Labrecque, Pierre-François; Tremblay, Cécile; Laffont, Benoit; Provost, Patrick; Routy, Jean-Pierre; Gilbert, Caroline
Abstract : Background: Because of factors only partly understood, the generalized elevated immune activation and inflammation characterizing HIV-1–infected patients are corrected incompletely with antiretroviral therapy (ART). Extracellular vesicles (EVs) including exosomes and microvesicles released by several cell types may contribute to immune activation and dysfunction. EV size, abundance, and content appear to differ according to infection phase, disease progression, and ART. Methods: We examined whether the size of EVs and the abundance of exosomes in plasma are associated with cell and tissue activation as well as with viral production. Acetylcholinesterase-bearing (AChE+) exosomes in plasma were quantified using an AChE assay. EV size was analyzed using dynamic light scattering. Proteins and microRNAs present in EVs were detected by Western blot and real-time polymerase chain reaction, respectively. Results: Exosomes were found more abundant in the plasma of ART-naive patients. EV size was larger in ART-naive than in ART-suppressed patients, elite controllers, or healthy control subjects. Both exosome abundance and EV sizes were inversely correlated with CD4/CD8 T-cell ratio and neutrophil, platelet, and CD4 T-cell counts and positively correlated with CD8 T-cell counts. A negative correlation was found between CD4 T-cell nadir and exosome abundance, but not EV size. Levels of miR-155 and miR-223 but not miR-92 were strongly correlated negatively with EV abundance and size in ART-naive patients. Conclusions: Monitoring of circulating EVs and EV-borne microRNA is possible and may provide new insight into HIV-1 pathogenesis, disease progression, and the associated inflammatory state, as well as the efficacy of ART and the treatments intended to reduce immune activation.